Simon Collier, Thomas E. Skidmore & Harold Blakemore (general editors): The Cambridge Encyclopedia of Latin America and the Caribbean - Jørgensen, Aage (Tidsskriftet Antropologi, 1993)
Simon Collier, Thomas E. Skidmore & Harold Blakemore (general editors): The Cambridge Encyclopedia of Latin America and the Caribbean Anmeldes af Aage Jørgensen